Literasi Digital dan Teknologi Komunikasi Interpersonal (Studi Kasus Penipuan melalui “Kencan Online” di Media Sosial) - DESSY KUSHARDIYANTI; Novy Khusnul Khotimah; Ana Humardhiana; Rani Ika Wijayanti; Misbah Binasdevi (LP2M IAIN Syekh Nurjati Cirebon, 2022)
The development of Information Communication Technology (ICT) became the trigger of changes in the process of interpersonal communication. Social Media became one of the platforms that many trigger the development of interpersonal communication process, especially in forming an intimate relationship.